Fish and Diadromy in Europe (ecology, management, conservation) - Dufour, Sylvie; Prevost, Etienne; Rochard, Eric; Williot, Patrick (Developments in Hydrobiology, 2008)
Most of the diadromous fish of the world have decreased in distribution and abundance since the beginning of the twentieth century. They are now threatened, and important conservation issues arise. The causes of these trends vary among species and basins but regional human impact (damming, pollution, fisheries) and global change (climate) are suspected to be responsible for these difficulties. This book contains selected papers from an international symposium organised by the Diadfish network held in Bordeaux (France) in 2005. Readers will find up-to-date information on the ecology, ecotoxicology and physiology of several diadromous species (Atlantic salmon, shads, lampreys, eels) and this whole group in Europe. Main impacts are also documented and analysed in case studies, and solutions or remediation actions are presented. .